Towards a Tradition of Sillimanian Literature - Casocot, Ian Rosales (Silliman Journal, 2022)
This article provides the motivation for a literary history of Silliman University, a specific example of regional literature that has remained a largely neglected part in the consideration of the Philippines’ national literary history, unappreciated in favor of the literary production and industry in the capital. The paper establishes Dumaguete as an important place in the Filipino literary geography and posits that there indeed exists a “Sillimanian” tradition of writing.